‘The Empire Floats Back’. Ariane Mnouchkine, her L’Indiade and the Nāṭyaśāstra - Gautam Chakrabarti (Cracow Indological Studies, 2018)
This paper seeks to explore certain prescriptive theorisations of the Nāṭyaśāstra and link them, in a comparative vein, with the often radical directorial approaches and experiments in post-WW2 European dramaturgical practice, especially as seen in the work of the eminent French metteur en scène, Ariane Mnouchkine (1939–), who founded the avant-garde stage ensemble Théâtre du Soleil in 1964, in Paris. Mnouchkine’s L’Indiade ou L’Inde de leurs Rêves (1987–1988), based on the learning experiences which Hélène Cixous—who wrote the play for and with her—and she had had in India during their stay and travels there, was an almost ground-breaking exploration of Indic motifs and stagement-configurations. The play will be viewed here from the perspective of ‘total theatre’, as also envisaged in the Nāṭyaśāstra. Finally, this paper will also seek to engage with theatrical and ritual boundaries in Mnouchkine’s work by looking at the reception of Indic forms of ritual-theatre in L’Indiade.